Analisis Representasi dan Interpretasi Makna Visual Dalam Iklan Marjan Edisi Ramadan 1444H: Analisis Semiotika Roland Barthes (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2024)
This research aims to identify and interpret the visual signs in the Marjan Syrup advertisement Ramadhan Edition 1444H using Roland Barthes' semiotic approach to understand the message to be conveyed to consumers. The type of research applied is qualitative description. The data analysis process was carried out by applying Roland Barthes' semiotic studies, allowing the observation of three levels of meaning (denotative, connotative, and mythical) in several scenes, visual signs, symbols, colors, and compositions contained in the Marjan Syrup advertisement, Ramadhan Edition 1444H. The research results concluded that this advertisement can be considered an achievement in communicating complex and in-depth messages through visual media.